Aposentadoria: o novo começo, expectativa e realidade. Uma análise com servidores técnicos-administrativos da UFG - Alves, Fleide Wilian Rodrigues (2016)
The work brings attached to itself a number of social protection mechanisms achieved by workers over the last two centuries. One of the most important is retirement, usually linked to aging, it presents as a social statute and a life transition that allocates the active worker erstwhile in the list of removed from the world of work. Of great importance in the personal and social context, this passage is a divider in the existence of workers, which has been enjoying retirement for more time due to increased life expectancy. This research aimed at understanding social aspects that permeate the retirement process of the Administrative Technical Education of Federal University of Goiás, in the period between his eminence and its recent acquisition.Regarding the worker about to retire, there was a discussion about the reasons that weighed in his decision, what are your expectations and plans for the future. After retirement, he was investigated as the worker just out of the labor market deals with your free time, if your plans and expectations have been met and as reestabelecem their family ties with their return home. Research has shown that the investigated statutory enjoy better quality of life when they are at work and in retirement, compared to CLT workers with the same training and educational level. This finding was justified by their income be higher, the job security and the possibility of coexistence of working times, and social times in their workplaces during the activity.